Application of Slope Maps as a Complement of Bathymetry: Example from the SW Atlantic - Esteban, Federico Damián (2017)
Topographic and bathymetric maps are commonly used to represent the morphology of the Earth's surface at different scales. However, there are specific geological aspects or features that may be masked or not sufficiently highlighted by solely those data. This article shows how the slope maps (or clinometrics), elaborated from the same bathymetric data, are a useful tool to overcome these limitations. To this purpose, we analysed an example of the South-Western Atlantic area where a slope map was produced from the General Bathymetric Chart of the Oceans (GEBCO) bathymetric grid. We show how the slope maps can significantly improve the morpho-bathymetric (or topographical) descriptions and allow extrapolation of interpretations or observations from analysis of seismic sections, identification or highlighting of small morpho-structures, and inference and the distinguishing of areas of diverse morphologies in relation with the sedimentary processes. We propose and discuss the use of slope maps as a complement to bathymetric maps for specific geological studies at macro- and meso-scales.